Trauma-informed forensic practice - Willmot, Phil; Jones, Lawrence (Issues in forensic psychology, 2022)
Section 1: Trauma and Offending 1. Childhood Maltreatment and its Links to Offending 2. Trauma, Violence and Gender 3. Trauma-Informed Risk Assessment and Intervention: Understanding the Role of Triggering Contexts and Offence-Related Altered States of Consciousness (ORASC) 4. Trauma, Personality Disorder and Offending; Section 2: Vulnerable Groups 5. From Care to Custody 6. Trauma and Intellectual Disability 7. Deafness and Trauma: A Journey to Equitable Trauma-Informed Care8. Trauma and Offending in UK Military Veterans; Section 3: Survival Responses 9. "When You Have Got Like Twenty Thousand Thoughts in Your Head, that One Little Thing Can Just Make It All Go Away": Trauma and Non Suicidal Self Injury in Forensic Settings 10. Trauma, Substance Use and Offending 11. Early Trauma, Psychosis and Violent Offending 12. Trauma and Sexual Offending: Causal Mechanisms and Change Processes 13. The Traumatic Impact of Violent Crime on Offenders; Section 4: Trauma-Responsive Treatment14. A Therapeutic Community Approach to Address Harmful Sexual Behaviour in Older Teenager 15. Containing Distress: Working with Compassion in a Prison-Based Democratic Therapeutic Community 16. Addressing Trauma with Young Adult Males in Custody: Implementing a Stepped Care Trauma-Informed Approach in a Young Offenders Institution 17. Trauma and the Experience of Imprisonment 18. Trauma Informed Community Services; Section 5: Organisational Issues19. Developing Trauma-Informed Youth Justice Services 20. Trauma-Informed Care in Hospitals 21. The Impact on Staff of Trauma-Informed Work in Forensic Settings 22. Trauma-informed Care and Culture Change in an NHS Forensic Service 23. Trauma and Restorative Justice 24. The Future of Trauma-Informed Forensic Practice